Impaired multimerization of human adiponectin mutants associated with diabetes. Molecular structure and multimer formation of adiponectin - Waki, Hironori; Yamauchi, Toshimasa; Kamon, Junji; Ito, Yusuke; Uchida, Shoko; Kita, Shunbun; Hara, Kazuo; Hada, Yusuke; Vasseur, Francis; Froguel, Philippe; Kimura, Satoshi; Nagai, Ryozo; et al. (The Journal of biological chemistry, 2003)
Adiponectin is an adipocyte-derived hormone, which has been shown to play important roles in the regulation of glucose and lipid metabolism. Eight mutations in human adiponectin have been reported, some of which were significantly related to diabetes and hypoadiponectinemia, but the molecular mechanisms of decreased plasma levels and impaired action of adiponectin mutants were not clarified. Adiponectin structurally belongs to the complement 1q family and is known to form a characteristic homomultimer. Herein, we demonstrated that simple SDS-PAGE under non-reducing and non-heat-denaturing conditions clearly separates multimer species of adiponectin. Adiponectin in human or mouse serum and adiponectin expressed in NIH-3T3 or Escherichia coli formed a wide range of multimers from trimers to high molecular weight (HMW) multimers. A disulfide bond through an amino-terminal cysteine was required for the formation of multimers larger than a trimer. An amino-terminal Cys-Ser mutation, which could not form multimers larger than a trimer, abrogated the effect of adiponectin on the AMP-activated protein kinase pathway in hepatocytes. Among human adiponectin mutations, G84R and G90S mutants, which are associated with diabetes and hypoadiponectinemia, did not form HMW multimers. R112C and I164T mutants, which are associated with hypoadiponectinemia, did not assemble into trimers, resulting in impaired secretion from the cell. These data suggested impaired multimerization and/or the consequent impaired secretion to be among the causes of a diabetic phenotype or hypoadiponectinemia in subjects having these mutations. In conclusion, not only total concentrations, but also multimer distribution should always be considered in the interpretation of plasma adiponectin levels in health as well as various disease states.